Bridging Islamic juristic differences in contemporary Islamic Finance - Soualhi , Younes (Brill Academic Publisher, 2012)
This article is an attempt to formulate a viable Sharīʿah framework for juristic diferences in contemporary Islamic inance. While acknowledging the legitimacy of juristic diferences as an inherent feature of Islamic law, such diferences could jeopardize a nascent Islamic inance industry, leading to what has come to be arbitrarily termed ‘Sharīʿah risk’ in Islamic inance. Two blocks appear to represent the two disputing sides since the launch of this industry, i.e., the Middle Eastern and South East Asian markets. hus, this article aims to bridge diferences in Islamic inance by proposing a framework and set of parameters that can be applied to all Islamic banking, Islamic capital market and takāful products. Apart from the outlined framework that aims to circumvent juristic disputes, this article concludes that juristic dispute resolution in Islamic inance will not be attainable until one can appreciate the legal and regulatory diferences in which Islamic inance operates worldwide.